Global research trends on the links between prostate cancer and postoperative urinary incontinence between 2014 and 2024: a bibliometrics and visualized study - FuQiang Li; DeSheng Zhu; QingHong Li; ZhiLong Zhong; WenTao Fan; Zekun Xu (Discover Oncology)
Abstract In recent years, the incidence of prostate cancer (PC) has increased. For patients suitable for surgery, surgical treatment is undoubtedly the first-choice. However, radical prostatectomy often leads to postoperative urinary incontinence. As a result, the issue of urinary incontinence following prostate cancer treatment has also come into focus. However, comprehensive and objective research on the overall state of UI after PC treatment remains scarce. This article aims to utilize bibliometrics to summarize and quantify the dynamic trends of UI in PC. We retrieved relevant literature on PC and UI from the Web of Science Core Collection database, spanning from January 1, 2014, to September 8, 2024, and analyzed bibliometric indicators such as the number of articles, journals, countries, institutions, authors, and keywords. A total of 2060 articles were included, and the study shows a continuous growth in the number of publications related to PC and UI, with the United States leading in this field. The Memorial Sloan Kettering Cancer Center is the institution with the highest research output, the journal "Urology" published the most articles, and author Matthew R Cooperberg has the highest research output. We recommend active collaboration between countries, institutions, and authors to conduct clinical and basic research. Keyword analysis indicates that current research is primarily focused on side effects following PC treatment, the application of artificial urinary sphincters, and the application of multiparametric magnetic resonance imaging in the field of PC and UI. We anticipate that side effects caused by PC treatment will continue to be a hot topic in future research. It has to be admitted that our study only included English literature in the Web of Science database, and there may be some selection bias.